2014
DOI: 10.1172/jci72305
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil AKT2 regulates heterotypic cell-cell interactions during vascular inflammation

Abstract: Interactions between platelets, leukocytes, and activated endothelial cells are important during microvascular occlusion; however, the regulatory mechanisms of these heterotypic cell-cell interactions remain unclear. Here, using intravital microscopy to evaluate mice lacking specific isoforms of the serine/threonine kinase AKT and bone marrow chimeras, we found that hematopoietic cell-associated AKT2 is important for neutrophil adhesion and crawling and neutrophil-platelet interactions on activated endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
117
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 53 publications
1
117
0
5
Order By: Relevance
“…The crawling of neutrophils followed by nucleation of platelets, shown sequentially in the Online Supplementary Movie S5, is similar to observations reported in mice in vivo. 3,4,14 We observed that platelet nucleation on arrested neutrophils in SS blood led to the formation of aggregates which partially occluded the microfluidic channels (Online Supplementary Figure S4). As shown previously in SCD mice in vivo, 3 RBCs were found to be trapped in these aggregates (Online Supplementary Figure S4D-F).…”
Section: Letters To the Editormentioning
confidence: 97%
See 2 more Smart Citations
“…The crawling of neutrophils followed by nucleation of platelets, shown sequentially in the Online Supplementary Movie S5, is similar to observations reported in mice in vivo. 3,4,14 We observed that platelet nucleation on arrested neutrophils in SS blood led to the formation of aggregates which partially occluded the microfluidic channels (Online Supplementary Figure S4). As shown previously in SCD mice in vivo, 3 RBCs were found to be trapped in these aggregates (Online Supplementary Figure S4D-F).…”
Section: Letters To the Editormentioning
confidence: 97%
“…The capture of activated platelets by adherent neutrophils is believed to play a role in the onset of vasoocclusion 3,4 in the venules of SCD mice. Using the twostep imaging strategy shown in Figure 1B,C, neutrophils were observed to arrest and then crawl in P-selectin, ICAM-1 and IL-8 coated microfluidic channels ( Figure 3A) which enabled nucleation of platelets on top of crawling neutrophils ( Figure 3B).…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Among several receptors and counter-receptors, the neutrophil-platelet association is primarily mediated by the interaction of neutrophil P-selectin glycoprotein ligand-1 (PSGL-1) and αMb2 integrin with platelet Pselectin and glycoprotein Ibα (GPIbα), respectively. 13 We have shown that AKT2 positively regulates the function of αMb2 integrin and P-selectin during vascular inflammation 12 and that combining hydroxyurea with AKT2 inhibition has immediate benefits in acute vaso-occlusive events and improves survival in SCD mice. 9 Although these results suggest that AKT2 inhibition may be a supplemental therapy for SCD patients with vaso-occlusive crises, no AKT2-specific inhibitor is currently available in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In neutrophils, which express AKT1 and AKT2, only AKT2 regulates cell migration, NADPH oxidase 2 activation, b2 integrin function, and neutrophil-platelet interactions under inflammatory conditions. 12,20 As a major isoform in endothelial cells, AKT1 modulates the activity of endothelial NO synthase and is involved in angiogenesis, acute inflammation, and atherosclerosis. [21][22][23] Human AKT isoforms share around 98% sequence homology with mouse proteins.…”
Section: Introductionmentioning
confidence: 99%